(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2021)
INTRODUCTION: In this article, a systematic review will be carried out to gather scientific evidence on the diagnostic evaluation process of Asperger’s Syndrome, aimed at the interdisciplinary work of the speech therapist and the psychologist. METHODS: Systematic review through the PRISMA method in databases such as Google Scholar, Scielo, Pubmed, Taylor & Francis Online, Sciencedirect and Springerlink, based on compliance with established criteria. RESULTS: They were carried out through a search in different databases using the PRISMA model that allows the selection of information. ANALYSIS AND DISCUSSION: The scientific evidence found regarding the diagnostic evaluation process of Asperger’s Syndrome is presented. CONCLUSIONS: Several studies associated with the subject were found where the diagnostic criteria and evaluation instruments are named that allow a specific diagnosis to be formulated and the intervention process to begin.